STRATEGI DUMAI VISION DALAM MEMPERTAHANKAN EKSISTENSINYA SEBAGAI TELEVISI LOKAL DI KOTA DUMAI - Suganda, Upi Destiana; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The history of television in Indonesia began in 1962, with the stipulation of the Minister of Information Decree No. 190A / KEP / Menpen / 1987 on limited channel broadcasts. This triggered the presence of local television ready to present broadcasts, information and culture from the region itself. Dumai Vision is one of the longest local television in Dumai City and still exists to this day. The purpose of this research is to know how Dumai Vision strategy in maintaining its existence as a local television in Dumai City. This research uses qualitative method with descriptive analysis. The object of this research is the local television Dumai Vision maintains its existence. The subjects of the study consisted of six persons selected using purposive techniques determined based on the criteria of informants who understood the local television part of Dumai Vision. Techniques of collecting data through interviews, observation, and documentation. The results of this study apply the theory of media ecology by Dimmick and Rothenbuhler which reveal that in order to maintain its existence, the media need the main life support sources namely, types of content (type of media content), types of audience (capital target audience) and capital (advertising revenue). In maintaining its presence in the local broadcasting industry in Dumai City, Dumai Vision runs a variety of strategies including: 1) Does a television program strategy, 2) Does strategy to attract viewers, 3) Does strategy to getting profit. Keyword: Strategy, Existence, Local Television, Media Ecology